HUBUNGAN TINGKAT KECEMASAN DENGAN TINGKAT KEMANDIRIAN ACTIVITIES OF DAILY LIVING PADA LANSIA - Tiara Sonza; Isna Aglusi Badri; Roza Erda (Universitas Fort De Kock, 2020)
International Journal of Geriatric Psychiatry found that more than 27% of elderly people experience difficulty in carrying out daily activities due to experiencing anxiety. This study aims to determine the relationship of anxiety levels with the level of independence Activities of Daily Living in the elderly. This type of research is analytic with cross sectional design, with a population of all elderly in the Work Area of Baloi Permai Public Health Center in Batam City in 2019 with a purposive sampling technique with a sample of 66 elderly people. The results obtained from 66 elderly people, elderly who did not experience anxiety independently numbered 39 elderly (59.1%), elderly who experienced mild anxiety with mild dependence totaling 20 elderly (30.3%), elderly who experienced mild anxiety with dependence moderate amounted to 1 elderly (1.5%), elderly who experienced moderate anxiety with moderate dependence amounted to 4 elderly (6.1%), elderly who experienced severe anxiety with heavy dependence amounted to 1 elderly (1.5%), elderly who experienced severe anxiety with a total dependence of 1 elderly (1.5%). Hypothesis test results using kruskall wallis obtained ρ value 0,000, indicating a significant relationship between the level of anxiety with the level of independence Activities of Daily Living in the elderly. Public health center can provide health education regarding the importance of checking the level of independence of the elderly and can carry out scheduled levels ofindependence during integrated healthcare center of the elderly to find out the fulfillment of daily activities in the elderly